Seafloor Hydrothermal Activity around a Large Non-Transform Discontinuity along Ultraslow-Spreading Southwest Indian Ridge (48.1–48.7° E) - Dong Chen; Chunhui Tao; Yuan Wang; Sheng Chen; Jin Liang; Shili Liao; Teng Ding (Journal of Marine Science and Engineering, 2021)
Non-transform discontinuity (NTD) is one category of tectonic units along slow- and ultraslow-spreading ridges. Some NTD-related hydrothermal fields that may reflect different driving mechanisms have been documented along slow-spreading ridges, but the discrete survey strategy makes it hard to evaluate the incidence of hydrothermal activity. On ultraslow-spreading ridges, fewer NTD-related hydrothermal activities were reported. Factors contributing to the occurrence of hydrothermal activities at NTDs and whether they could be potential targets for hydrothermal exploration are poorly known. Combining turbidity and oxidation reduction potential (ORP) sensors with a near-bottom camera, Chinese Dayang cruises from 2014 to 2018 have conducted systematic towed surveys for hydrothermal activity around a large NTD along the ultraslow-spreading Southwest Indian Ridge (SWIR, 48.1–48.7° E). Five new potential hydrothermal anomaly sites (2 inferred and 3 suspected) of high or low temperature and the previously inferred Sudi hydrothermal field occurred in diverse morphotectonic settings along a 78 km long ridge axis. The calculated vent frequency (Fs, sites/100 km) was ~7.7 over the entire study area, higher than the modified value (Fs ≈ 6.5) between 48 and 52° E of SWIR. Even only for the 54 km long large NTD, three hydrothermal anomaly sites yielded an Fs of ~5.6, which is higher than that of most ridge sections and is comparable to some fast-spreading ridges with high-resolution surveys. This indicates that NTDs along ultraslow-spreading ridges could be promising areas in fertilizing hydrothermal activities. Moreover, the deeply penetrating faults on the rift valley walls and strain-focused areas may contribute to the formation of NTD-related hydrothermal circulations. We suggest that NTDs along ultraslow-spreading ridges may be potential targets for further exploration of hydrothermal activities and seafloor sulfide deposits.